(untitled) (College of Basic Education Research Journal, 2025)
Dialogue is an element of narrative style , poets employed it in their poems since pre-Islamic era , through early Islamic period , to reach Umayyad era , Its use increased among Abbasid poets , to mention but one, Muslim ibn al-Walid , This research explores effectiveness of dialogue in his poetry and how he employs it as a means to express ideas and feelings deeply embedded within his poet . Study aims to uncover methods and techniques used by poet to employ dialogue .